The rediscovery of Lepisanthes unilocularis (subgen. Otophora; Sapindaceae), a species endemic to Hainan, China. (7th May 2018) - Wang, Qing‐Long; Tang, Huan; Wang, Mao‐Yuan; Wang, Zhu‐Nian; Yang, Qing
Abstract : Lepisanthes unilocularis, endemic to Hainan, China, was considered to be extinct but has now been rediscovered after nearly 80 years. The morphological features and taxonomy of the species are described and discussed in this paper.